Preparation and characterization of electrically conductive films from agar-agar (carrageenan) - Maizatul Amira, Mansor. (Universiti Malaysia Sarawak, UNIMAS, 2013)
In this study, commercially available agar-agar (carrageenan) was used to produce electrically conductive agar-based thin film. Agar strips as the starting material were gelatinized in water by heating, and glycerol was then added as a plasticizer to produce agar-based thin films. A thin layer of copper sulphide (CuS) was then deposited on the surface agar-based film to form electrically conductive films upon drying at 60°C in the oven for 24 hours.